Relationship of sperm morphology assessed by strict criteria and outcome of artificial [intrauterine] insemination - Nayak, Vedavathy; Gunasheela, Devika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The aim of the study was to investigate the relationship between sperm morphology assessed by strict criteria and the outcome of artificial insemination. Methods: 495 consecutive intrauterine insemination (IUI) cycles done for 417 couples in a 1-year period in Gunasheela IVF Center were studied. In all cases controlled ovarian stimulation and hCG timed IUI were performed. In all cases the inseminating motile sperm count after sperm preparation (at least one sample) was 20 million/ml and motility was 90% Grade A. Sperm morphology was assessed by strict criteria. Results: Overall the pregnancy rates were significantly higher in cases with ≥14% normal morphology (23%) and in cases with 10-13% normal morphology (14%). This was in contrast to the pregnancy rates in cases with <10% normal morphology group (8%). Further follow up of the outcome of pregnancies between the ≥10% normal morphology and <10% normal morphology groups did not show any increased loss of pregnancies/anomalies in the <10% normal morphology group but this was not statistically significant as the number of pregnancies in the <10% normal morphology group was very less (8 out of 87). Conclusions: These results emphasize the significance of sperm morphology as a predictor of pregnancy outcome (esp. pregnancy rates) in the IUI outcome.